Secondary technical resectability of colorectal cancer liver metastases after chemotherapy with or without selective internal radiotherapy in the randomized SIRFLOX trial. Issue 13 (19th August 2019) - Garlipp, B.; Gibbs, P.; Van Hazel, G. A.; Jeyarajah, R.; Martin, R. C. G.; Bruns, C. J.; Lang, H.; Manas, D. M.; Ettorre, G. M.; Pardo, F.; Donckier, V.; Benckert, C.; et al.
Abstract : Background: Secondary resection of initially unresectable colorectal cancer liver metastases (CRLM) can prolong survival. The added value of selective internal radiotherapy (SIRT) to downsize lesions for resection is not known. This study evaluated the change in technical resectability of CRLM with the addition of SIRT to FOLFOX‐based chemotherapy. Methods: Baseline and follow‐up hepatic imaging of patients who received modified FOLFOX (mFOLFOX6: fluorouracil, leucovorin, oxaliplatin) chemotherapy with or without bevacizumab (control arm) versus mFOLFOX6 (with or without bevacizumab) plus SIRT using yttrium‐90 resin microspheres (SIRT arm) in the phase III SIRFLOX trial were reviewed by three or five (of 14) expert hepatopancreatobiliary surgeons for resectability. Reviewers were blinded to one another, treatment assignment, extrahepatic disease status, and information on clinical and scanning time points. Technical resectability was defined as at least 60 per cent of reviewers (3 of 5, or 2 of 3) assessing a patient's liver metastases as surgically removable. Results: Some 472 patients were evaluable (SIRT, 244; control, 228). There was no significant baseline difference in the proportion of technically resectable liver metastases between SIRT (29, 11·9 per cent) and control (25, 11·0 per cent) arms ( P = 0·775). At follow‐up, significantly more patients in both arms were deemed technically resectable compared with baseline: 159 of 472 (33·7 per cent) versus 54 of 472 (11·4 per cent) respectively ( P = 0·001). More patients were resectable in the SIRT than in the control arm: 93 of 244 (38·1 per cent) versus 66 of 228 (28·9 per cent) respectively ( P < 0·001). Conclusion: Adding SIRT to chemotherapy may improve the resectability of unresectable CRLM. Abstract : Secondary resection of initially unresectable colorectal cancer liver metastases (CRLM) can prolong survival. This study of 472 patients suggests that chemotherapy with FOLFOX with or without bevacizumab may improve the technical resectability rate of CRLM, especially in patients with an initial hepatic tumour burden of 25 per cent or less, and that this effect is enhanced substantially by adding selective internal radiotherapy to systemic chemotherapy. Might improve resectability Abstract : Antecedentes: La resección secundaria de metástasis hepáticas de cáncer colorrectal ( colorectal cancer liver metastases, CRLM) inicialmente irresecables puede prolongar la supervivencia. Se desconoce el valor añadido de la radioterapia interna selectiva ( selective internal radiation therapy, SIRT). Este estudio evaluó el cambio en la resecabilidad técnica de las CRLM secundario a la adición de SIRT a una quimioterapia tipo FOLFOX. Métodos: Las pruebas de radioimagen basales y durante el seguimiento de pacientes tratados con un régimen FOLFOX modificado (mFOLFOX6: fluorouracilo, leucovorina, oxaliplatino) ± bevacizumab (grupo control) versus mFOLFOX6 (± bevacizumab) más SIRT usando microesferas de resina de yttrium‐90, en el ensayo de fase III SIRFLOX, fueron revisadas por 3‐5 (de 14) cirujanos expertos hepatobiliares para determinar la resecabilidad. Los expertos efectuaron la revisión de forma ciega unos respecto a otros en relación con la asignación al tratamiento, estado de la enfermedad extra‐hepática y situación clínica en el momento del estudio radiológico. La resecabilidad técnica se definió como ≥ 60% de revisores evaluando las metástasis del paciente como quirúrgicamente resecables. Resultados: Fueron evaluables un total de 472 pacientes (control, n = 228; SIRT, n = 244). No hubo diferencias significativas basales en la proporción de metástasis hepáticas técnicamente resecables entre SIRT (29/244; 11, 9%) y el grupo control (25/228; 11, 0%: P = 0, 775). Durante el seguimiento y en ambos brazos de tratamiento, un número significativamente mayor de pacientes se consideraron técnicamente resecables en comparación con la situación basal (54/472 (11, 4%) basal y 159/472 (33, 7%) al seguimiento). Hubo más pacientes resecables en el grupo SIRT que en el control (93/244 (38, 1%) y 66/228 (28, 9%); P < 0, 001, respectivamente). Conclusión: La adición de SIRT a la quimioterapia puede mejorar la resecabilidad de las CRLM irresecables.